Perintah Komandan Terhadap Bawahan dalam Kasus Penembakan Polisi Duren Tiga Perspektif Filsafat Etika Immanuel Kant - Fitri, Nur Annisa; Arman (Jurnal Filsafat Indonesia, 2023)
Richard Eliezer's status as a Justice Collaborator regarding the murder case of Brigadier Yosua, he explained that the shooting had been planned by the defendant Ferdy Sambo, as stated in his testimony at the trIal. he even said that at the time of the shooting, he ordered Ricard to beat, not shoot. the occurrence of two different versions of the story, in this study we will not look at two different statements, let the judges judge the facts of the trIal. However, in this paper, the author will analyze the superior's orders to subordinates using Immanuel Kant's ethics. The method used in this study is descriptive qualitative, by collecting various kinds of secondary data that are relevant to the problem. In this study the authors used literature study. The result is Kant's view of ethics, which in accordance with this case is personal autonomy (human freedom), in this theory it is explained that all human beings on this earth must be autonomous and free, as meant by Ricard Eliezer, but they are framed by units, in this case POLRI , in police culture there is always something called obedience by subordinates to superiors, so we often hear the Commander's ready sentence, so that it is difficult for subordinates to refuse.